A Study of Geopotential Geoid in the Peninsular of Malaysia - Ses, Shahrum (Fakulti Ukur dan Harta Tanah, 1990)
Geo idal heights can be computed for a single point value or a grid of values.A program to compute goidal heights from a set of high degree potential coefficients was developed. Backward recurrence formulae have been used to evaluate the value of normalized Legendre functions.The regional and global geopotential geo id evaluated from the available sets of potential coefficients were shown in the form of contoured maps. The computed geo idal heights derived from different sets of potential coefficients were compared with Doppler derived values at six points in Peninsular Malaysia. The results indicate that, of the models tested OSU86 gives the best solution to the geopotential geoid in the region